EDUKASI MODEL RAMBUT SESUAI SYARIAH DI UMKM BARBERSHOP MAS NO PASAR TUMPANG KABUPATEN MALANG - Nahdiyah, Naila; Affif Wahyudi (STAI Ma'had Aly Al-Hikam Malang, 2023)
Abstract This service aims to accompany haircut services at Mas NO Barbershop in Tumpang village and provide an understanding of haircut models at Mas NO Barbershop in Tumpang village that are in accordance with Islamic law. This service is an activity carried out in order to develop community members with assistance procedures including preparation, planning, implementation and assessment. Based on the results of the service that has been carried out, it can be concluded that it is very important to share knowledge related to the sharia economic side of the haircut service business in Mas NO Barbershop which provides shaving services to its customers according to the needs and desires of hair style trends that customers like. In general, many of the shaving style trends that customers are interested in do not comply with Islamic law, which is caused by barbershop business actors or customers not understand the shaving model that is in accordance with Islamic law. Keywords: Barbershop Services & Islamic Hairstyles Abstrak Pengabdian ini bertujuan mendampingi layanan potong rambut di Mas NO Barbershop desa Tumpang dan memberikan pemahaman model potongan rambut di Mas NO Barbershop desa Tumpang yang sesuai dengan syariat Islam. Pengabdian ini merupakan kegiatan yang dilakukan dalam rangka mengembangkan anggota masyarakat dengan prosedur pendampingan di antaranya persiapan, perencanaan, pelaksanaan dan penilaian.. Berdasarkan hasil pengabdian yang telah dilakukan, maka dapat disimpulkan bahwa sangat penting berbagi pengetahuan terkait sisi ekonomi syariah pada usaha jasa potong rambut pada Mas NO Barbershop yang memberikan layanan cukur kepada pelanggannya sesuai dengan kebutuhan dan keinginan trend model rambut yang disukai oleh pelanggan, yang pada umumnya trend model cukur yang diminati oleh pelanggan, banyak yang tidak sesuai dengan syariat Islam, yang disebabkan karena pelaku usaha barbershop ataupun pelanggan tidak memahami model cukur yang sesuai syariat Islam. Kata Kunci: Jasa Barbershop & Model Rambut Sesuai Islam